The Contribution of Islamic Law in Resolving Aceh Customary Disputes Over Joint Property Division Due to Divorce - Afrizal, Afrizal (Institut Agama Islam Al-Aziziyah Samalanga, 2023)
In Aceh, joint property is referred to as